Peritoneal dialysis and exchange transfusion in a neonate with argininosuccinic aciduria. Issue 3 (March 1976) - Francois, B; Cornu, G; de Meyer, R
Abstract : Peritoneal dialysis rapidly reduced blood ammonia concentration in this child with arginino-succinic acid-lyase deficiency, whereas exchange transfusion did not. Yet this reduction in plasma ammonia level did not produce clinical improvement. We speculate that the effects of ammonia intoxication on the highly susceptible neonatal metabolism are due to an accumulation of toxic products and to an altered energy metabolism. Both aspects must be considered in any attempt to treat congenital hyperammonaemia.